THE EFFECT OF USING POSTERS ON STUDENTS’ ACHIEVEMENT IN WRITING HORTATORY EXPOSITION TEXT - Muhammad Akhyar Rasyidi; Siti Aisah Ginting (Universitas Negeri Medan, 2015)
This study was focused on the investigation of The Effect of Using Posterson Students’ Achievement in Writing Hortatory Exposition Text. This study aimsat findings whether using posters as the media affect the students’ writingachievement or not. This study used an experimental research design with twovariables, namely using posters as independent variable and students’achievement in writing hortatory exposition text as dependent variable. Thepopulation of this study was the 2014/2015 second year students (grade XI) ofSMA Budi Agung Medan and 60 students were taken as the sample. The samplewas divided into two groups, experimental group and control group. Theexperimental group was taught by using posters while the control group wastaught without using posters. The instrument used in this study was a written test.The data were taken by administering the pre-test and post-test to both control andexperimental groups. These data were analyzed by using t-test. The result ofcomputing the t-test obviously showed that t-observed is higher than t-table (3.12> 1.67) with the degree of freedom 58 (df = N-2) at the level significance 0.05 onetail test. It showed that the using of posters affects the students’ achievement inwriting hortatory exposition text.